2023
DOI: 10.3390/ijerph20075281
|View full text |Cite
|
Sign up to set email alerts
|

Liver Function in Patients with Long-Term Coronavirus Disease 2019 of up to 20 Months: A Cross-Sectional Study

Abstract: The long-term laboratory aspects of the effects of coronavirus disease 2019 (COVID-19) on liver function are still not well understood. Therefore, this study aimed to evaluate the hepatic clinical laboratory profile of patients with up to 20 months of long-term COVID-19. A total of 243 patients of both sexes aged 18 years or older admitted during the acute phase of COVID-19 were included in this study. Liver function analysis was performed. Changes were identified in the mean levels of alanine aminotransferase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 30 publications
1
6
0
1
Order By: Relevance
“…This liver marker alteration, indicative of hepatocyte damage and systemic inflammation, is evidenced by increased levels of various interleukins and IFN-λ in hospitalized patients [33]. Severe COVID-19 cases, similarly to our findings, show raised AST, ALT, and GGT levels with reduced albumin, although mean albumin remained normal in different studies [34]. AST's role as a liver marker is complex due to its muscle production, especially given that Long COVID-19 patients often face fatigue and muscle weakness [35].…”
Section: Important Findings and Literature Reviewsupporting
confidence: 87%
“…This liver marker alteration, indicative of hepatocyte damage and systemic inflammation, is evidenced by increased levels of various interleukins and IFN-λ in hospitalized patients [33]. Severe COVID-19 cases, similarly to our findings, show raised AST, ALT, and GGT levels with reduced albumin, although mean albumin remained normal in different studies [34]. AST's role as a liver marker is complex due to its muscle production, especially given that Long COVID-19 patients often face fatigue and muscle weakness [35].…”
Section: Important Findings and Literature Reviewsupporting
confidence: 87%
“…Statistical analysis showed that COVID-19 impacted liver function in both male and female patients within the severe category, specifically through elevated alanine transaminase (ALT) and aspartate transaminase (AST) levels. Interestingly, age within this group emerged as a potential contributing factor, with male aged 66-90 exhibiting a greater degree of liver impairment [42]. Bilirubin levels also displayed age-and gender-specific nuances.…”
Section: Discussionmentioning
confidence: 98%
“…37 Although there is no universal definition of PCC, its prevalence has been described in up to 45% of COVID-19 patients with unresolved symptoms at 4 months. 38 In a cross-sectional study of 246 patients with long COVID, 39 74 exhibited elevated ALT levels, and 63 exhibited elevated AST levels; among these patients, those who required hospitalization during the acute illness were more likely to have liver enzyme derangements. Bende et al 40 demonstrated increased liver stiffness, viscosity, and steatosis using liver elastography in approximately one-third of patients with persistent COVID-19 symptoms at 3 to 11 weeks.…”
Section: Covid-19 and Liver Injurymentioning
confidence: 99%